Effect of betel leaf meal (Piper Betle L.) as feed additive on milk composition and somatic cell count of subclinical mastitis - Abdul Alim Yamin; Asep Sudarman; Dwierra Evvyernie (Fakultas Peternakan, Universitas Padjadjaran, 2022)
The aim of this experiment was to study the effect of betel leaf meal (BLM) as feed additive on milk composition and somatic cell count of subclinical mastitis infected cow. The experiment design was a completely randomized design with five dietary treatments of BLM level and four replications in concentrate feed. The treatments were T0 (without betel leaf meal, as control), T1 (2% of betel leaf meal every day), T2 (4% of betel leaf meal every day), T3 (2% of betel leaf meal skip two days), and T4 (4% of betel leaf meal skip two days). Milk samples from the infected quarter would be analyzed every week of the experiment. Parameters measured were milk composition and somatic cell count. Data were analyzed by using analysis of variance (ANOVA) and the differences among treatments were examined by Duncan's multiple range test. Results showed that in T1 decreased somatic cell count by 83%, but the addition of BLM did not significantly affect milk composition. It could be concluded that the addition of 2% of BLM as a feed additive has the potency to prevent mastitis in lactating cows.